Photovoltaic integrated electric vehicles: assessment of synergies between solar energy, vehicle types and usage patterns - Sagaria, Shemin (2022)
Electric vehicles are promoting sustainable developments in the automotive industry. But the short driving range has been an inconvenience to the electric vehicle (EV) users. This paper evaluates the potential of Photovoltaic integrated into EV in real-world conditions to assess energy consumption, range and EV's charging frequency for battery and fuel cell powertrain configurations. A simulation model is developed, which estimates the energy production through onboard Photovoltaics, energy consumption, and range under diverse driving profiles for five different vehicle types, ranging from Micro-car, 5 seaters light-duty vehicle, Shuttle and heavy-duty vehicles. The results showed that the range increased with reduced energy consumption and charging frequency with onboard Photovoltaics for battery powertrain configuration. The range improved by 30-50% for Microcar and 30-100% for the 5-seater vehicle with the private driving profile. Simultaneously, for Shuttle, an increase in the range between 5 and 15% is reported. On the contrary, the results indicated the fuel cell powertrain configuration does not present an added value with onboard Photovoltaics. Further analysis showed that the higher irradiance rates improved the operational period of Photovoltaic integrated into EV by 5 more days than standard EV. Finally, the economic analysis revealed that Photovoltaics integrated into EV is profitable, reaching the break-even point on the additional photovoltaics expense before the half-life of the vehicle, which makes the total ownership cost lower than a standard EV for its lifetime.